Internal verification of coating quality in conformity with the requirements of the EN 1090 standard - Horvat, Marko, inženjer strojarstva; Srpak, Dunja; Kondić, Veljko; Pus, Igor (2018)
The requirements for the quality of protection on metal structures in terms of durability, reliability and efficiency require from the manufacturer to define certain procedures and verification of anticorrosion protection activities. Today, the criteria used to evaluate the success of the protection and the general quality of the structure are the criteria listed in the EN 1090 standard and in the compatible standards related to the realization and protection of metal structures. The article briefly describes the basis of the requirements of the standard, the eligibility criteria for the protection of structures and it also gives a practical example of the verification process through preparation, implementation and control.
Bibliografija: 11 jed.
Abstract.
Keywords: Metalne konstrukcije -- Zaštita metala -- Zaštita od korozije